Processed airborne radio-echo sounding data from the FISS 2015 survey covering the Foundation Ice Stream, Bungenstock Ice Rise, and the Filchner Ice Shelf system, West Antarctica (2015/2016) - Nicholls, Keith; Robinson, Carl; Corr, Hugh; Jordan, Tom (NERC EDS UK Polar Data Centre, 2021)
An airborne radar survey was flown during the austral summer of 2015/16 over the Foundation Ice Stream, Bungenstock Ice Rise, and the Filchner ice shelf as part of the 5-year Filchner Ice Shelf System (FISS) project. This project was a NERC-funded (grant reference number: NE/L013770/1) collaborative initiative between the British Antarctic Survey, the National Oceanography Centre, the Met Office Hadley Centre, University College London, the University of Exeter, Oxford University, and the Alfred Wenger Institute to investigate how the Filchner Ice Shelf might respond to a warmer world, and what the impact of sea-level rise could be by the middle of this century. The 2015/16 aerogeophysics survey acquired ~7,000 line km of aerogeophysical data with a particular focus on the Foundation Ice Stream. Our Twin Otter aircraft was equipped with dual-frequency carrier-phase GPS for navigation, radar altimeter for surface mapping, wing-tip magnetometers, and a new ice-sounding radar system (PASIN-2). We present here the full radar dataset consisting of the deep-sounding chirp and shallow-sounding pulse-acquired data in their processed form, as well as the navigational information of each trace, the surface and bed elevation picks, ice thickness, and calculated absolute surface and bed elevations. This dataset comes primarily in the form of NetCDF and georeferenced SEGY files. To interactively engage with this newly-published dataset, we also created segmented quicklook PDF files of the radar data. : ** Instrumentation and Processing: Radar data were collected using the new bistatic PASIN-2 radar echo sounding system mounted on the BAS Twin Otter aircraft "VP-FBL" and operating with a centre frequency of 150 MHz and using a 4-microseconds, 13 MHz bandwidth linear chirp. Chirp compression was applied using a Blackman window to minimise sidelobe levels, resulting in a processing gain of 10 dB. The chirp data was processed using a coherent averaging filter (commonly referred to as unfocused Synthetic Aperture Radar (SAR) processing) with Doppler beam sharpening to enhance the signal to clutter ratio of the bed echo and improve visualisation. The received chirp of 4 microseconds, 13 MHz bandwidth data was compressed, filtered, and decimated from the original trace acquisition rate of 156.25 Hz to 5Hz, equivalent to ~11m in along-track spacing. The chirp data is best suited to assess the bed and internals in deep ice conditions. The coherent pulse-data (0.1 microseconds) was processed using a coherent averaging filter. This data is best used to assess the internal structure and bed in shallow ice conditions. The bed reflector was first automatically depicted on the chirp data using a semi-automatic picker in the PROMAX software package. All the picks were afterwards checked and corrected by hand if necessary. The picked travel time was then converted to depth using a radar wave speed of 168 m/microseconds and a constant firn correction of 10 m. Where possible, the ice surface location within the radargrams was calculated using lidar measurements of surface elevation. In areas where lidar data was not available, the location of the surface reflection was picked directly from the radargram. The origin of the elevation measurement can be found in the 'surface_source_layerData' variable in this NetCDF, and is composed of either: 0 = LIDAR, 1 = interpolated LIDAR for gaps ~55 m, 2 = radar. ** Coordinates and Positions: The coordinates provided in the NetCDF for the surface and bed elevation for each radar trace are in longitude and latitude (WGS84, EPSG: 4326). The navigation attributes for the radar data in the NetCDF are in projected X and Y coordinates (Polar Stereographic, EPSG: 3031), as follows: Latitude of natural origin: -71 Longitude of natural origin: 0 Scale factor at natural origin: 0.994 False easting: 0 False northing: 2082760.109 The coordinates in the SEGY data are also in projected X and Y coordinates (Polar Stereographic, EPSG: 3031), although note that these are in integer format due to the SEGY limitations (see section below). Positions are calculated for the phase centre of the aircraft antenna. All positions (Longitude, Latitude and Height) are referred to the WGS1984 ellipsoid. ** Dataset: Please note: Due to the unstable nature of SEGY-formatted data and its uncertain long-term future, as well as the issues documented below, we also provide the full radar data in NetCDF format. The dataset provided here consists of three parts: a NetCDF file per flightline, two SEGY files per flightline (one chirp and one pulse), and one quicklook PDF file per flightline. These are described in more details below. - NetCDF: The NetCDF files contain the processed deep-sounding chirp and shallow-sounding pulse-acquired data in their processed form, as well as the associated metadata, navigational information (in both EPSG: 3031 and WGS84 EPSG: 4326), and the associated radar-related information for each trace (e.g. surface/bed elevation and picks, ice thickness, aircraft altitude, range to surface, time of trace) which are provided as separate attributes in the NetCDF file. The navigational position of each trace comes from the surface files, and the processed GPS files when no surface information was provided or when duplicates were found in the surface file (see Quality section above). Note that for these, interpolation of the navigational data might have been required to match closely the Coordinated Universal Time (UTC) of each trace in the surface files. No data is shown as "-9999" throughout the files. NetCDF attributes: - 'traces': Trace number for the radar data (x axis) - 'fast_time': Two-way travel time (y axis) (units: microseconds) - 'x_coordinates': Cartesian x-coordinates for the radar data (x axis) (units: meters in WGS84 EPSG:3031) - 'y_coordinates': Cartesian y-coordinates for the radar data (x axis) (units: meters in WGS84 EPSG:3031) - 'chirp_data': Radar data for the processed (coherent) chirp (units: power in dBm) - 'pulse_data': Radar data for the processed (coherent) pulse (units: power in dBm) - 'PriNumber': Incremental integer reference number related to initialisation of the radar system that permits the processed segy data and picked surface and bed to be linked back to raw radar data (also known as PriNum) (units: arbitrary - integers) - 'longitude_layerData': Longitudinal position of the trace number (units: degree_east in WGS84 EPSG:4326) - 'latitude_layerData': Latitudinal position of the trace number (units: degree_north in WGS84 EPSG:4326) - 'UTC_time_layerData': Coordinated Universal Time (UTC) of trace (also known as resTime) (units: seconds) - 'terrainClearanceAircraft_layerData': Terrain clearance distance from platform to air interface with ice, sea or ground (also known as resHt) (units: meters) - 'aircraft_altitude_layerData': Aircraft altitude (also known as Eht) (units: meters relative to WGS84 ellipsoid) - 'surface_source_layerData': Origin of the elevation measurement with 0 = LIDAR, 1 = interpolated LIDAR, 2 = radar - 'surface_altitude_layerData': Ice surface elevation for the trace number from radar altimeter and LiDAR (units: meters relative to WGS84 ellipsoid) - 'surface_pick_layerData': Location down trace of surface pick (BAS system) (units: microseconds) - 'bed_altitude_layerData': Bedrock elevation for the trace number derived by subtracting ice thickness from surface elevation (units: meters relative to WGS84 ellipsoid) - 'bed_pick_layerData': Location down trace of bed pick (BAS system) (units: microseconds) - 'land_ice_thickness_layerData': Ice thickness for the trace number obtained by multiplying the two-way travel-time between the picked ice surface and ice sheet bed by 168 m/microseconds and applying a 10 meter correction for the firn layer (units: meters) - SEGY: The SEGY files are provided for the processed-chirp and pulse-acquired data and have been georeferenced using the navigational position of each trace from the surface files, and the processed GPS files when no surface information was provided in the surface files. Note that for these, interpolation of the navigational data might have been required to match closely the Coordinated Universal Time (UTC) of each trace in the surface files. SEGY header description: - byte number 1-4 and 5-8 (SEQWL and SEQWR): Trace number for the SEGY - byte number 9-12 (FFID): PriNumber for each SEGY trace - byte number 73-76 (SRCX): Cartesian x-coordinates for each SEGY trace (units: meters in WGS84 EPSG:3031) - byte number 77-80 (SRCY): Cartesian y-coordinates for each SEGY trace (units: meters in WGS84 EPSG:3031) - byte number 115-116 (NSMP): Number of samples for each SEGY trace - byte number 117-118 (SI): Sampling interval for each SEGY trace Note that the current version of the SEGY (Revision 1.0) does not yet allow to store double-precision floats in the "Source X/Y" trace headers and thus the X and Y positions for each trace are rounded to the nearest integer when exporting the data. This will affect the accurate position of each trace in the SEGY data, however the precise X and Y position of each trace can be obtained from the NetCDF files if necessary. When loading in the georeferenced SEGY files into seismic-interpretation software for data visualisation and analysis, the user might be warned that duplicate traces are found within the data and that this might cause "bad performance". This is caused by the rounding of the X and Y positions in the SEGY headers as explained above and should only affect the position of a relatively small amount of traces. - Quicklook: The quicklook PDF files were produced to allow for a quick visualisation of the radar data and the position of each flightline with regards to the rest of the survey flightlines. The radar image in the PDF is from the processed chirp radar data and is split into 25-km segments for the FISS 2015 survey. These segments (and the radar images associated with them) are the same as those shown on the Polar Airborne Geophysics Data Portal. : ** Instrument: Radar data were collected using the bistatic PASIN-2 (Polarimetric radar Airborne Science Instrument 2) radar echo sounding system mounted on the BAS Twin Otter aircraft "VP-FBL" and operating with a centre frequency of 150 MHz and using a pulse-coded waveform at an effective acquisition rate of 312.5 Hz and a bandwidth of 13 MHz. The Pulse Repetition Frequency was 15,635 Hz (pulse repetition interval: 64 microseconds). ** Antenna configuration: 8 transmitters (4x port side and 4x starboard side) 12 receivers (8x wings and 4x belly) Transmit power: 1 kW into each antennae Maximum transmit duty cycle: 10% at full power ** Waveform details: Five waveforms, 4uS Tukey port, 4uS Tukey starboard, 1uS Tukey port, 1uS Tukey starboard, 1 uS Tukey antenna 1 (port). ** Radar receiver configuration: Receiver vertical sampling frequency: 22 MHz (resulting in sampling interval of 45.4546 ns) Receiver coherent stacking: 25 Receiver digital filtering: -50 dBc at Nyquist (11 MHz) Effective PRF: 312.5 Hz (post-hardware stacking) Sustained data rate: 10.56 Mbytes/second : - Average spacing between radar traces: 11 m - Radar centre frequency: 150 MHz - Radar bandwidth: 13 MHz - Radar Receiver vertical sampling frequency: 22 MHz - Absolute GPS positional accuracy: ~0.1 m (relative accuracy is one order of magnitude better). Banking angle was limited to 10 degrees during aircraft turns to avoid phase issues between GPS receiver and transmitter.